An Exploratory Study on Customers Attitudes Towards Generic Products - Nor Azila, Mohd Noor (1996)
The purpose of this research is to examine customers’ attitudes towards generic products. These products are different from traditional grocery product marketing because they are unbranded items, receive little, if any, promotion, branding, packaging and product improvement expenditures. Furthermore, generics have received little academic research attention compared with other brands. Therefore, the main objective of this study was to explore customers’ attitudes towards generics on various issues such as price, quality, packaging, promotion, value, product ranges, package information and package sizes. In this research, a sample of 110 Kwik Save customers was generated through street interviews in Bridge of Allan area. To represent generic products, the No Frills’ product range was used. The data for this research was mainly gathered from interviews conducted and from previous work in this area. The analysis for this research is presented in the form of; frequency count, cross-tabulations and Chi-square test, in respect of achieving the objectives of this study. The results revealed that, generic buyers have favourable attitudes towards the cheaper price of generics, product quality, good value for money and sufficient package information. The majority of generic buyers have infavourable attitudes towards the limited package sizes of generics and the limited product ranges offered. On demographic characteristics, generic buyers can be differentiate based on age groups. Generics achieved a high level of awareness among buyers and in-store observation was the most popular way given by customers on how they became aware of generics. Generics have gained a good purchase satisfaction among buyers and this lead to their intention to buy again whether from Kwik Save or other stores. Based on the results and conclusion made, the researcher suggested that there is a need to carry out similar study with samples drawn from nationally representative population and generic product non-buyers as well. Some methodological changes also recommended to improve the findings of this study.